Enhanced Photoelectrocatalytic H2 Evolution over Two‐Dimensional MoS2 Nanosheets Loaded on Cu‐Doped CdS Nanorods. Issue 3 (20th December 2018) - Tian, Haoyang; Liang, Jintao; Ma, Xuli; Cao, Lele; Hu, Xueyan; Gao, Mengting; Yang, Huimin; Liang, Zhenhai
Abstract: Transition‐metal ion doping and efficient decoration by using a co‐catalyst have been proven to effectively inhibit the recombination of photogenerated electron‐hole pairs and broaden the visible‐light response region. Here, we have constructed MoS2 nanosheets decorated on a copper‐doped CdS nanorod composite as a noble‐metal‐free photoelectrocatalyst. This kind of composite material was constructed through a simple solvothermal method. The morphology, structure, chemical states, photoelectrochemical properties, and other properties were tested by using a diverse range of analytical techniques. Owing to the Cu 2+ doping and the excellent electron‐capturing ability of MoS2, 5 % MoS2 /Cu−CdS (with 7 % Cu 2+ doping in CdS) exhibits excellent hydrogen evolution reaction with a rate of 10.18 mmol h −1 g −1, which is about 48 times higher than that of pure CdS. A significant increase in the photoelectrochemical performance of the composite catalytic material benefits from the synergistic effect between CdS and MoS2 and fast interfacial charge transfer, owing to the Cu 2+ doping. These findings provide a new thought for further research of the ion doping in photoelectrocatalytic field. Abstract : Photo finish : A catalyst made of MoS2 nanosheets loaded on Cu‐doped CdS nanorods is synthesized through a facile two‐step solvothermal approach. The working electrode is formed by loading a certain amount of catalyst on fluorine tin oxide. A significant increase in the photoelectrochemical performance is observed, owing to the synergistic effect between CdS and MoS2 and fast interfacial charge transfer from the Cu 2+ doping.